2018
DOI: 10.1029/2018gl077632
|View full text |Cite
|
Sign up to set email alerts
|

The Intensity, Directionality, and Statistics of Underwater Noise From Melting Icebergs

Abstract: Freshwater fluxes from melting icebergs and glaciers are important contributors to both sea level rise and anomalies of seawater salinity in polar regions. However, the hazards encountered close to icebergs and glaciers make it difficult to quantify their melt rates directly, motivating the development of cryoacoustics as a remote sensing technique. Recent studies have shown a qualitative link between ice melting and the accompanying underwater noise, but the properties of this signal remain poorly understood.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…First, we take advantage of the fact that submarine melting of glacier ice also generates underwater noise due to the impulsive release of pressurized air bubbles into the water (Urick, 1971;Deane et al, 2014;Pettit et al, 2015). Glowacki et al (2018) have demonstrated that the melt noise has an α-stable distribution. Importantly, the characteristic exponent of the α-stable distribution indicates proximity to a melting source.…”
Section: Automatic Detection Of Calving Eventsmentioning
confidence: 99%
“…First, we take advantage of the fact that submarine melting of glacier ice also generates underwater noise due to the impulsive release of pressurized air bubbles into the water (Urick, 1971;Deane et al, 2014;Pettit et al, 2015). Glowacki et al (2018) have demonstrated that the melt noise has an α-stable distribution. Importantly, the characteristic exponent of the α-stable distribution indicates proximity to a melting source.…”
Section: Automatic Detection Of Calving Eventsmentioning
confidence: 99%
“…Measurements are insensitive to lighting conditions such as fog; cloud coverage; and the polar night, humidity and intensity of precipitation. Moreover, acoustic signals recorded in glacial bays and fjords also contain signatures of ice melt associated with impulsive bubble release events (Urick, 1971;Tegowski et al, 2011;Deane et al, 2014;Pettit et al, 2015;Glowacki et al, 2018). While currently no quantitative models exist to estimate melt rates from underwater noise, the potential idea to simultaneously measure submarine melting and calving, two major processes acting at the glacier-ocean interface, is worth mentioning.…”
Section: Studying Iceberg Calving With Underwater Noisementioning
confidence: 99%
“…The number of beams was set to 2000, with launching angles ranging from −80 to 80 • with respect to the sea surface. Guided by previous geomorphological studies ( Görlich, 1986;Staszek and Moskalik, 2015), we assumed that the dominant sediment type in the study area is a clayey silt; density, sound speed and attenuation were taken to be 1.4 g cm −3 , 1530 m s −1 and 0.1 dB m −1 kHz −1 , respectively (Hamilton, 1970(Hamilton, , 1976. The absorption of sound in seawater is negligible for the low frequencies considered here (e.g., Ainslie and McColm, 1998).…”
Section: Noise Transmission Lossmentioning
confidence: 99%
“…Moreover, acoustic signals recorded in glacial bays and fjords also contain signatures of ice melt associated with impulsive bubble release events (Urick, 1971;Tegowski et al, 2011;Deane et al, 2014;Pettit et al, 2015;Glowacki et al, 2018).…”
Section: Studying Iceberg Calving With Underwater Noisementioning
confidence: 99%